Fundamental interactions and physical properties of starch, poly vinyl alcohol and montmorillonite clay based nanocomposites prepared using solution mixing and melt extrusion - Ali, Samer Shaur (Kansas State University, 2010)
Plastics from petroleum sources are the main raw materials used for producing food packaging films. But these plastic films cause a great environmental concern due to their non-degradable nature and non-renewable source. Biodegradable polymers like starch can be used as a base material which can replace petroleum based plastics packaging. In this study, starch (0-80%) and polyvinyl alcohol (PVOH) (20-100%) were used as base polymers to produce nanocomposites. Glycerol (30%) and sodium montmorillonite (0-20%) were used as a plasticizer and nano-filler, respectively. Nanocomposites were produced through two methods: solution and melt extrusion method. Extrusion method resulted in greater exfoliation of nanocomposites than solution method because it provided more shear stress to disrupt the layered silicate structure. In extrusion method, a lab scale extruder was used to produce these nanocomposites and films were made by casting. Process parameters, including screw speed (200-400 RPM) and barrel temperature (145-165[superscript]oC), were varied systematically. X-ray diffraction (XRD) and transmission electron microscopy (TEM) were conducted to characterize the nanostructure of these nanocomposites. Thermal characterization of these films was carried out through differential scanning calorimetric (DSC) studies. Results from XRD and TEM explained the phenomenon of intercalation and exfoliation in these nanocomposites. Structural and thermal data indicated important role for Na[superscript]+MMT along with process parameters in controlling exfoliation and glass transition temperature of the nanocomposites. These results also helped in understanding the fundamental interactions among all the components. The tensile strength and elongation at break of films ranged from 4.72 to 23.01MPa and 63.40 to 330.15% respectively, while water vapor permeability ranged from 1.68 to 0.79g.mm/kPa.h.m[superscript]2. These results provide a great understanding for further improvements in order to bring these films close to commercial plastic films which have superior tensile strength (10-80MPa), elongation at break (200-800%) and water vapor permeability (0.002- 0.05g.mm/kPa.h.m[superscript]2). The cost for polyethylene is approximately $0.70/lb while the raw material cost for this starch based films is approximately $0.85/lb.
Keywords: Nanocomposites; Extrusion; Biodegradable films; Starch; Polyvinyl alcohol; Agriculture, Food Science and Technology (0359)